Preparing Catholic Educators for Flourishing in a Secularized Society: A Case Study - Roberts, Amy; Kilbane, Clare; Rook, Rebecca (Verbum Vitae, 2024)
As culture experiences secularization, and the importance of religion and prevalence of people holding religious worldviews diminishes, the work of forming Catholics who can live out their professional and Christian vocations as teachers in different types of schools becomes simultaneously more crucial and more complex. This article explores the importance of preparing Catholic teachers for employment in contemporary educational settings in the United States to respond to accelerating secularization. It argues that the Catholic Church’s vision for education can be implemented within the limitations of US education policy, especially through the careful preparation of Catholic teachers in Catholic Educator Preparation Programs (EPPs). First, it presents the unique context of US education, illustrating the setting in which such programs function and the associated challenges. Next, it shares the Church’s vision for well-prepared Catholic educators, identifying three key anthropological conflicts linked to secularization and explaining how the Church’s teaching on Catholic education as presented by Archbishop Michael Miller’s “Five Essential Marks of Catholic Schools” provides needed guidance for EPPs located in Catholic universities. Next, it offers a case study presenting one EPP’s efforts to respond to secularization through its program redesign according to a framework that integrates Miller’s Five Marks. Finally, it explains the difficulties facing Catholic EPPs as they integrate their mission with the demands of professional preparation.